Transisi dari Pengendalian Gejala Menuju Pemulihan Harga Diri pada Pasien Pasca Psikotik dengan Riwayat Kekerasan Verbal - Tanan, Rosmitha; Kutanggas, Jeane Rosalia; Tukayo, Harumitha; Gobai, Alfrida (Journal of Telenursing (JOTING), 2025)
This study aims to describe the transition from symptom control to self-esteem recovery through the application of activities of daily living therapy (ADL) in post-psychotic patients with a history of verbal abuse. The research method used a descriptive case study design on one outpatient at the Timika Community Health Center with a nursing diagnosis of chronic low self-esteem, post-psychotic patients, and verbal abuse. The results showed an increase in the RSES score from 7 (low category) to 18 (moderate category) and positive behavioral changes in the form of increased independence, pride in work performance, and improved social interactions with family. Emotional support from family plays a crucial role in strengthening the patient's self-confidence and motivation to participate in daily activities. In conclusion, ADL therapy accompanied by family support is effective in helping post-psychotic patients transition from the symptom control phase to the recovery of self-esteem and psychosocial functioning.   Keywords: Low Self-Esteem, Verbal Abuse, Post-Psychotic, Psychosocial Recovery, ADL Therapy